BEYOND THE CLASSROOM: INTEGRATING UNIVERSAL DESIGN FOR LEARNING INTO INCLUSIVE EXTRACURRICULAR ACTIVITIES - Dewa Gede Nata Raditya (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study investigates how the Universal Design for Learning (UDL) framework can be applied to extracurricular activities in inclusive junior high schools in Indonesia. Despite the increasing emphasis on inclusive education, most UDL implementations remain limited to classroom instruction. Through a literature review approach, this study promotes and designs inclusive extracurricular programs across three domains: athletics, hobby-based academics, and performing arts. These programs incorporate UDL’s three core principles—Engagement, Representation, and Action & Expression—while also considering students’ cognitive styles and developmental needs. The findings demonstrate that extracurricular activities, when inclusively designed, can strengthen students’ sense of identity, support their psychosocial development, and foster equitable opportunities for both academic and non-academic achievement, including for students with disabilities. This approach offers valuable guidance for educators and policymakers committed to advancing inclusive practices beyond the classroom.